Cell identity dynamics and insight into insulin secretagogues when employing stem cell-derived islets for disease modeling - Wang, Chencheng; Abadpour, Shadab; Aizenshtadt, Aleksandra; Dalmao-Fernandez, Andrea; Høyem, Merete; Wilhelmsen, Ingrid; Stokowiec, Justyna; Olsen, Petter Angell; Krauss, Stefan; Chera, Simona; Ghila, Luiza; Ræder, Helge; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Stem cell-derived islets (SC-islets) are not only an unlimited source for cell-based therapy of type 1 diabetes but have also emerged as an attractive material for modeling diabetes and conducting screening for treatment options. Prior to SC-islets becoming the established standard for disease modeling and drug development, it is essential to understand their response to various nutrient sources in vitro. This study demonstrates an enhanced efficiency of pancreatic endocrine cell differentiation through the incorporation of WNT signaling inhibition following the definitive endoderm stage. We have identified a tri-hormonal cell population within SC-islets, which undergoes reduction concurrent with the emergence of elevated numbers of glucagon-positive cells during extended in vitro culture. Over a six-week period of in vitro culture, the SC-islets consistently demonstrated robust insulin secretion in response to glucose stimulation. Moreover, they manifested diverse reactivity patterns when exposed to distinct nutrient sources and exhibited deviant glycolytic metabolic characteristics in comparison to human primary islets. Although the SC-islets demonstrated an aberrant glucose metabolism trafficking, the evaluation of a potential antidiabetic drug, pyruvate kinase agonist known as TEPP46, significantly improved in vitro insulin secretion of SC-islets. Overall, this study provided cell identity dynamics investigation of SC-islets during prolonged culturing in vitro, and insights into insulin secretagogues. Associated advantages and limitations were discussed when employing SC-islets for disease modeling.